2020
DOI: 10.3390/aerospace7070095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal Cycle and Ultraviolet Radiation on 3D Printed Carbon Fiber/Polyether Ether Ketone Ablator

Abstract: The extreme heating environment during re-entry requires an efficient heat shield to protect a spacecraft. The current method of manufacturing a heat shield is labor intensive. The application of 3D printing can reduce cost and manufacturing time and improve the quality of a heat shield. A 3D printed carbon fiber/polyether ether ketone (CF/PEEK) composite was proposed as a heat shield material. The aim was to develop a heat shield and the structural member as a single structure while maintaining the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…While these requirements at first glance suggest using metals, these are damaged by atomic oxygen which is available in LEO [14,15], making objects from pure polymers or polymer coatings often more reliable. Amongst them, several applications are based on polyether ether ketone, a high-temperature polymer which was successfully in thermal cycles from −70 • C to +140 • C, making it suitable as a heat shield material for the re-entry of microsatellites or other spacecraft [16]. Other authors tested in addition polyetherimide (PEI) ULTEM 9085, PEI modified ULTEM 1010, and poly(ether ketone ketone) and found these materials also to withstand a short heat flux of 100 W cm −2 for 30 s, making them also suitable for the potential use as heat shields [17].…”
Section: Introductionmentioning
confidence: 99%
“…While these requirements at first glance suggest using metals, these are damaged by atomic oxygen which is available in LEO [14,15], making objects from pure polymers or polymer coatings often more reliable. Amongst them, several applications are based on polyether ether ketone, a high-temperature polymer which was successfully in thermal cycles from −70 • C to +140 • C, making it suitable as a heat shield material for the re-entry of microsatellites or other spacecraft [16]. Other authors tested in addition polyetherimide (PEI) ULTEM 9085, PEI modified ULTEM 1010, and poly(ether ketone ketone) and found these materials also to withstand a short heat flux of 100 W cm −2 for 30 s, making them also suitable for the potential use as heat shields [17].…”
Section: Introductionmentioning
confidence: 99%
“…Both metals and polymers are not easily chosen for such conditions—while metals may be impaired by atomic oxygen in the LEO and impaired by cosmic rays, many polymers have glass transition temperatures that are too low or suffer from mechanical problems upon temperature cycling [ 21 , 22 ]. This is why polyether ether ketone (PEEK) is often used, a high-temperature material that was suggested as a heat shield for the re-entry of microsatellites since it could withstand temperature cycles between −70 °C and +140 °C [ 23 ]. In another study, further high-temperature polymers were tested, such as polyetherimide (PEI) ULTEM 9085, PEI-modified ULTEM 1010, or poly(ether ketone ketone) (PEKK), and also found suitable for similar thermal conditions [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on its different magnitude and period time, the exposure to temperature of 3D-printed composites could affect the mechanical behavior of the materials differently. Researchers usually use different thermal cycling profiles to study the behavior of aerospace vehicles such as satellite components, which depend on their case study or thermal cycling test apparatus [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…At various temperatures, experimental photos from post-mortem photographs, scanning electron microscopy, and high-speed films were used to investigate various failure behaviors such as micro-buckling, kinking, and fiber breakage. In more recent experimental research by [ 6 ], 3D-printed CF/PEEK was exposed to thermal cycling and then evaluated using tensile and arc heating tests. It was reported that the thermal cycle resulted in decreased tensile strength and the length of the samples increased after the heating test.…”
Section: Introductionmentioning
confidence: 99%